Diseases - Shoals, James; Shoals, James (Broomall, Pennsylvania: Mason Crest, 2019)
Nobody likes to get sick! And yet, diseases are a constant source of fascination for us all. Whether it's the cold bug that kept you home from school or the genetic disease called hemophilia that sparked the Russian Revolution, human illnesses are an amazing and complex area of study. Diseases will introduce you to many ways in which the human body can malfunction, and also teach you about what doctors can do to fix it."--Provided by publisher